2018
DOI: 10.1177/0361198118783863
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Individual Economic Activities and Regional Market Structures Caused by Rural Road Improvements in Cambodia

Abstract: In rural areas of developing countries, most individuals engage in farming of staple foods and trading them in their local markets for daily earnings. If a road is improved, what would happen to those markets and the local populations’ economic activities? This study aimed to examine the effects of rural road improvements on local economic activities and market structures in rural areas of Cambodia using quantitative and qualitative data collected from face-to-face interviews. The data included both individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…According to [21]- [23], the improved roads most especially the rural roads provide easier access to markets for farmers and these markets are located alongside the main roads where vehicles pass frequently. Thus, motorists and other road users often stop to buy agricultural produce before they continue their journey which sustains the roadside markets.…”
Section: Road Improvement Increase the Roadside Market For Agricultur...mentioning
confidence: 99%
“…According to [21]- [23], the improved roads most especially the rural roads provide easier access to markets for farmers and these markets are located alongside the main roads where vehicles pass frequently. Thus, motorists and other road users often stop to buy agricultural produce before they continue their journey which sustains the roadside markets.…”
Section: Road Improvement Increase the Roadside Market For Agricultur...mentioning
confidence: 99%
“…Expanding the network of roads and highways increases the availability of resources and facilitates the movement of goods and services, leading to increased economic efficiency [1]. Road improvements have been shown to increase individual economic activity and boost regional economic growth by facilitating market access and trade [2]. [3] found that infrastructure development, especially road infrastructure, significantly encourages economic growth.…”
Section: Introductionmentioning
confidence: 99%